The impact of social stigmas and health vulnerabilities on the lives of people with leprosy (Research, Society and Development, 2022)
Introduction: Leprosy is an infectious disease caused by the bacillus Mycobacterium leprae. It is considered a public health problem in Brazil and in other countries because of its slow evolution, high transmission rate, and physical, sociocultural, economic, and emotional/psychological repercussions. Objective: To identify the impact of social stigmas and health vulnerabilities on the lives of leprosy patients. Method: This is an integrative literature review. The data search was conducted in April 2022 by three independent authors through the Medical Literature Analysis and Retrieval System Online (MEDLINE) under the Pubmed interface and the Virtual Health Library (VHL) Regional Portal, using the descriptors: leprosy OR mycobacterium leprae AND social vulnerability AND social determinants of health. Results: The results are presented by means of synoptic tables, containing title, country and year, main findings and level of evidence of the selected articles. In total, eleven articles were selected that responded to the research problem. Conclusion: Leprosy is linked to several stigmas that surround low self-esteem, fear and social exclusion, corroborating for a great interference between the relations of leprosy patients with society, since the isolation of this population was a method used for a long time.